Optimality of Supermarket Inventory Policies Under Stochastic Demand in Uganda:A Case Study of Milk Powder Product - Mubiru, Kizito Paul; Kariko-Buhwezi, Bernard; Lating, Peter (PROCEEDING OF THE EIGTH OPERATIONS RESEARCH SOCIETY FOR EASTERN AFRICA (ORSEA) INTERNATIONAL CONFERENCE, 1998)
Effective inventory management requires cost-effective methods in determining the optimal ordering decisions of cycle inventories in a stochastic demand environment. In this paper, an inventory model with stochastic demand is developed to analyze the ordering decisions of milk powder in supermarkets given a periodic review inventory system under stochastic demand. Adopting a Markov decision process approach, the states of a Markov chain represent possible states of demand for milk powder product. The decision of when to order is made using dynamic programming over a finite period planning horizon. The approach demonstrates the existence of an optimal state-dependent ordering policy as well as the corresponding total inventory costs.
Keywords: Modeling, Optimization, inventory policy, stochastic demand